Survival in familial idiopathic pulmonary fibrosis and fibrotic hypersensitivity pneumonitis - Reis Estrella, Deborah; Mancuzo, Eliane; de Amorim Correa, Ricardo; Tibana, Regina; Soares, Maria Raquel; de Castro Pereira, Carlos Alberto (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background: Familial pulmonary fibrosis (FPF) is defined as the occurrence of any interstitial lung disease (ILD) in two or more first- or second-degree relatives. Although the most frequently reported phenotype is idiopathic pulmonary fibrosis (IPF), other forms of ILD have been identified, such as fibrotic hypersensitivity pneumonitis (fHP). This study aims to explore survival between patients with IPF and fHP substratified by presence or absence of self-reported familial pulmonary fibrosis. METHODS: Family history was acquired systematically, and patients were stratified by IPF or fHP according to specific guidelines. Clinical data on pulmonary function and imaging were collected during the first follow-up evaluation of patients. All cases were reviewed in multidisciplinary meetings. Other ILD diagnosis was excluded. RESULTS: A total of 198 participants were included: 88 with IPF and 110 with fHP. In the IPF group, 36 had familial forms (F-IPF), and in the fHP group, 30 had familial fHP (F-fHP). The median follow-up time was 37 (3 - 1200) months. The variables age (hazard ratio [HR]: 1.03; 95% CI: 1.01 - 1.06; p = 0.01), FVC% (HR: 0.96; 95% CI: 0.94 - 0.98; p < 0.01), SpO2% (HR: 0.86; 95% CI: 0.76 - 0.97; p < 0.02), and family history of pulmonary fibrosis (HR: 1.79; 95% CI: 1.09 - 2.93; p = 0.02) were associated with mortality and were controlled before performing the survival curves. The median survival for the FPF group was 46 months compared to 75 months for the non-familial group (p = 0.009). Conclusion: patients with familial presentations of IPF and fHP have significantly lower survival compared to patients with non-familial presentations of the same diseases. In clinical practice across many countries, genetic testing is not widely available, so family history should always be investigated.